Aetiological role of viral and bacterial infections in acute adult lower respiratory tract infection (LRTI) in primary care. Issue 1 (14th October 2005) - Creer, D D; Dilworth, J P; Gillespie, S H; Johnston, A R; Johnston, S L; Ling, C; Patel, S; Sanderson, G; Wallace, P G; McHugh, T D
Abstract : Background: Lower respiratory tract infections (LRTI) are a common reason for consulting general practitioners (GPs). In most cases the aetiology is unknown, yet most result in an antibiotic prescription. The aetiology of LRTI was investigated in a prospective controlled study. Methods: Eighty adults presenting to GPs with acute LRTI were recruited together with 49 controls over 12 months. Throat swabs, nasal aspirates (patients and controls), and sputum (patients) were obtained and polymerase chain reaction (PCR) and reverse transcriptase polymerase chain reaction (RT-PCR) assays were used to detect Streptococcus pneumoniae, Mycoplasma pneumoniae, Chlamydia pneumoniae, Legionella pneumophila, influenza viruses (AH1, AH3 and B), parainfluenza viruses 1–3, coronaviruses, respiratory syncytial virus, adenoviruses, rhinoviruses, and enteroviruses. Standard sputum bacteriology was also performed. Outcome was recorded at a follow up visit. Results: Potential pathogens were identified in 55 patients with LRTI (69%) and seven controls (14%; p<0.0001). The identification rate was 63% (viruses) and 26% (bacteria) for patients and 12% (p<0.0001) and 6% (p = 0.013), respectively, for controls. The most common organisms identified in the patients were rhinoviruses (33%), influenza viruses (24%), and Streptococcus pneumoniae (19%) compared with 2% (p<0.001), 6% (p = 0.013), and 4% (p = 0.034), respectively, in controls. Multiple pathogens were identified in 18 of the 80 LRTI patients (22.5%) and in two of the 49 controls (4%; p = 0.011). Atypical organisms were rarely identified. Cases with bacterial aetiology were clinically indistinguishable from those with viral aetiology. Conclusion: Patients presenting to GPs with acute adult LRTI predominantly have a viral illness which is most commonly caused by rhinoviruses and influenza viruses.